O Professor Coordenador: Um Estudo Sobre Identidade - Cardozo, Marcel Fernando Inácio (2006)
This work intend to comprehend the process of constitution of de identity of the teacher who acts as a coordinator at the public school system in the of stole São Paulo. To perform this searching, it was adopted the theoretical methodological references of the historical-dialectic materialism, in the field of social psychology, especially the Theory of Identity, of Ciampa. This searching adopted methods of investigation, record and analysis of the data based on the adopted references. So, it is necessary to declare the option to work with only one subject, and it is usual in the searching of identity with the selection of one teacher coordinator. This teacher has 16 years of experience in the pedagogical practice in the teaching system of São Paulo and, nowadays, acts as a coordinator in a cicle-II and high school at the São Paulo State public system of teaching. The picking up of the data was developed in three meetings and took 34 days, utilizing the narrative of the history of life as a method of searching. In the very analysis process it was possible to connect pieces of the talking of the interviewed teacher with the theoretical categories of the Theory of Identity, this way making possible to go ahead will the interpretations based on that theory. Besides, it is important to consider that process of analysis contributed to a better comprehension of the different social marks present at the constitution of the subject. This is an indicator that interferes decisively at the action of the teacher coordinator, and permits to identify, in this case of study, a lot of factors which determine a way of action capable of producing a considerable improving of the teaching offered by the school, as it gives priority to the student and his learning process